Molecular dynamics analysis of the thermal conductivity of graphene and silicene monolayers of different lengths - Yeo, Jing Jie (2014)
Nano- to micron-sized monolayered materials of both carbon (graphene) and silicon (silicene) were modeled with molecular dynamics. Graphene was modeled using an optimized parameterization of the Tersoff potential, while silicene was modeled using parameterizations of the Tersoff potential for silicon. Thermal conductivities were determined from direct non-equilibrium molecular dynamics. The present results indicate that as the lengths of both materials increased, the corresponding thermal conductivities increased as well, such that graphene had far higher thermal conductivity than silicene across all length scales. Armchair and zigzag chiralities in both graphene and silicene had no significant differences in thermal conductivities, given the fact that these monolayered materials were modeled with infinite widths. Graphene was found to possess significantly higher thermal conductivities than silicene at every length scale and chirality, and this can be attributed to the higher phonon group velocities of the dominant acoustic modes in graphene, shown through studies on the vibrational density of states and the phonon dispersion curves.